2019
DOI: 10.3390/jcm8050695
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Tumor Angiogenesis and Immune Microenvironment in Non-Functional Pituitary Endocrine Tumors

Abstract: Cavernous sinus (CS) invasion is an aggressive behavior exhibited by pituitary neuroendocrine tumors (PitNETs). The cause of CS invasion in PitNETs has not been fully elucidated. The tumor immune microenvironment, known to promote aggressive behavior in various types of tumors, has not been examined for PitNETs. Vascular endothelial growth factor (VEGF)/VEGF receptor (VEGFR) signaling is strongly associated with the tumor immune microenvironment. In the present study, these molecular and histopathological char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 57 publications
(76 reference statements)
4
60
3
Order By: Relevance
“…These findings support a role for infiltrating M2-macrophages in the angiogenesis of PitNETs, as previously described in other cancers [13, 27, 42, 44, 80, 83]. We found no association between PitNET-infiltrating CD163+ macrophages and cavernous sinus invasion, although a recent study showed more CD163+ macrophages in invasive NF-PitNETs than in non-invasive tumours [68].…”
Section: Discussionsupporting
confidence: 92%
“…These findings support a role for infiltrating M2-macrophages in the angiogenesis of PitNETs, as previously described in other cancers [13, 27, 42, 44, 80, 83]. We found no association between PitNET-infiltrating CD163+ macrophages and cavernous sinus invasion, although a recent study showed more CD163+ macrophages in invasive NF-PitNETs than in non-invasive tumours [68].…”
Section: Discussionsupporting
confidence: 92%
“…Programmed death receptor 1 (PD-1)/programmed death ligand 1 (PD-L1) is a pair of negative costimulatory factors that play a key role in the tumor immune escape mechanism. PD-L1 can be expressed in tumor microenvironment cells and can inhibit the activation of T cells through binding to PD-1, which also weakens the entire immune system of patients [33][34][35]. Immune checkpoint therapy prevents PD-1/PD-L1 binding in tumors and restores the cytotoxicity of T cells [36].…”
Section: Discussionmentioning
confidence: 99%
“…As such, the immune TME needs to be carefully characterized in the different groups of pituitary tumors prior to understanding its exact role. To date, studies aimed at defining the immune TME of pituitary tumors are rare and mostly rely on the immunohistological characterization of cells based on a single or a few immune markers that are not sufficient to define the complexity of immune cell lineages (Table 2) [37,38,39,40,41,42,43,44]. Moreover, the classification of pituitary tumors (including the use of IHC for diagnosis) and of their aggressiveness varies across different studies, as does the interpretation of the immune infiltrate, with some studies considering the immune infiltrate in terms of either its presence or absence, while other studies have looked at the quantity or the intensity of the various markers.…”
Section: Immune Infiltrative Cellsmentioning
confidence: 99%
“…Therefore, the combined use of immunotherapies and drugs targeting angiogenesis is emerging as a novel strategy for the treatment of numerous cancers [8,49]. Interestingly, such observations may also have important implications for the treatment of pituitary tumors as it was recently reported that pituitary tumors invading the cavernous sinus show a higher expression of VEGF, VEGFR1, and PD-L1, as well as having a higher number of TAMs [44]. This suggests that, at least in the case of the aggressive non-functioning pituitary tumors analyzed in their study, tumor angiogenesis is associated with an immunosuppressive TME, and that immunotherapy combined with therapies aimed at obtaining vascular normalization should be envisioned in such tumor types.…”
Section: Immune Infiltrative Cellsmentioning
confidence: 99%